Poisson-weighted exponential distribution and its application on claim count data - Hossein Zamani ,; Noriszura Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
This paper introduces the distribution of a Poisson-weighted exponential, P-WE, which is obtained by mixing the distributions of the Poisson and the weighted exponential, WE. The parameter estimation via the method of moments and the maximum likelihood procedure is shown, and the application of the P-WE on insurance claim count data is considered